Single-cell transcriptomics of Pacific white shrimp (Litopenaeus vannamei) hepatopancreas reveal immune and metabolic responses to AHPND-causing Vibrio parahaemolyticus - Aldersey, Johanna E.; Abernathy, Jason W.; Lange, Miles D.; García, Julio C.; Shoemaker, Craig A.; Beck, Benjamin H. (Frontiers in Immunology, 2026)
BackgroundThe shrimp aquaculture industry is severely impacted by acute hepatopancreatic necrosis disease (AHPND) caused by the bacterium Vibrio parahaemolyticus. The hepatopancreas is a multi-functional organ with roles in digestion, immunity, molting and reproduction. The mechanism by which the pathogen causes disease, and the host immune response is not completely understood. Therefore, we set out to characterize the cells of the hepatopancreas and host response to bacterial infection at single-cell resolution.MethodsFirst, hepatopancreas from three healthy Pacific white shrimp (Litopenaeus vannamei) were sampled to produce a single-cell transcriptomic atlas. Then, the hepatopancreas from three V. parahaemolyticus infected and two mocked treated shrimp were sampled for an infection study. Primary cell suspensions were produced, and single-cell libraries were generated using the 10x Genomics Chromium X controller with GEM-X 3’ gene expression reagents. Libraries were sequenced and data aligned to the shrimp reference genome using Cell Ranger. Seurat and clusterProfiler were used for downstream analyses.ResultsThe atlas consists of 11,006 quality cells that were grouped into nine clusters, and represent the hepatopancreas epithelial cells, myocytes and hemocytes. The infection study generated 16,368 quality cells and was integrated with the atlas for 27,374 cells grouped into nine clusters. Cells from the infected shrimp exhibited expression of immune related genes including diverse pathogen recognition receptors and humoral proteins, including hemocyanin, proteases and C-type lectins. We also found that cells expressed factors that the PirA/B toxins present in the infective V. parahaemolyticus may bind to, such as fatty acid binding protein (Fabp). In response to infection, energy metabolism (oxidative phosphorylation) was altered in a cluster-dependent manner which may reflect immune or pathogenic processes.ConclusionsWe characterized the cells types of the hepatopancreas and examined the transcriptomic response to a virulent isolate of V. parahaemolyticus, the causative agent of AHPND. Cells exhibited significant humoral immune responses suggesting the role of these genes in immune responsiveness to the pathogen. The outcomes will inform future functional studies and provide insights toward novel preventative measures or treatments.